CHARACTERISTICS OF THE IDEAL HEAD OF FAMILY ACCORDING TO THE QUR'AN AND SUNNAH - Bahri, Samsul; Pratama, Riky (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research aims to explore and analyze the concept of the ideal head of family from an Islamic perspective based on the teachings of the Qur'an and Sunnah. Using a qualitative library research method, this study examines primary Islamic sources and various exegetical literature and hadith commentaries to identify the fundamental characteristics of an ideal family head. The findings reveal that the ideal head of family in Islam does not merely function as a breadwinner but carries multidimensional responsibilities encompassing spiritual, moral, social, and economic aspects. Ten key characteristics of the ideal family head are identified: piety towards Allah SWT, responsible leadership function (qawwamah), ability to provide both material and emotional sustenance, role as primary educator, exemplary moral conduct (uswah hasanah), effective communication skills and implementation of consultation principles (shura), fairness toward all family members, high patience in facing trials, ability to maintain family stability and security, and sincerity in performing all functions and responsibilities. The research findings affirm that the Islamic concept of family leadership offers a comprehensive framework relevant for creating families characterized by tranquility (sakinah), affection (mawaddah), and mercy (rahmah) amid the complexity of contemporary social challenges.